Using Linear Regression to Identify Critical Demographic Variables Affecting Patient Safety Culture From Viewpoints of Physicians and Nurses - Chih-Yi Chi; Hsin-Hung Wu; Chih-Hsuan Huang; Yii-Ching Lee (Baqiyatallah University of Medical Sciences, 2017)
Background: The issues of patient safety and healthcare quality have become increasingly important around the world since the 1990s. Many hospitals manage to reduce the number of adverse events (AEs) that can threaten patient safety in healthcare organizations. Assessing the existing patient safety culture gives hospital management a clear vision of an organization's strengths and weaknesses. The Safety Attitudes Questionnaire, with its good psychometric properties and great internal consistency, has been used extensively to assess the patient safety culture in healthcare organizations. Objective: Physicians and nurses form the core staff of each organization. With different demographic variables, they might perceive patient safety culture differently. This study purposed to identify critical demographic variables from the viewpoints of physicians and nurses that significantly influence the patient safety culture in a regional teaching hospital in Taiwan. Methods: Linear regression with forward selection was employed in this study to focus on all physicians and nurses using results of a 2015 internal survey in the case hospital. Ten demographic variables were the independent variables, and seven dimensions of the Chinese version of the Safety Attitudes Questionnaire were dependent variables. Results: Four out of 10 demographic variables had significant impacts on 6 out of 7 dimensions (with the exception of emotional exhaustion) from the Safety Attitudes Questionnaire. "Supervisor/manager" and "experience in position" followed by "age" were viewed by physicians and nurses as the most critical variables affecting the patient safety culture in this regional teaching hospital in Taiwan. Conclusion: Assessing an organization's current patient safety culture provides a significant value to improving patient safety. This study revealed that "supervisor/manager" and "experience in position" are the 2 most important demographic variables influencing the patient safety culture. Hospital management should take heed of the suggestions of staff members regarding these characteristics to continuously enhance their patient safety culture.